Hostile Media Perceptions of Friendly Media Do Reinforce Partisanship. (March 2020) - Kleinnijenhuis, Jan; Hartmann, Tilo; Tanis, Martin; van Hoof, Anita M. J.
The hostile media effect (HME) entails that partisanship incites hostile perceptions of media content. However, other research underscores that partisans selectively turn to like-minded media, resulting in a friendly media phenomenon (FMP). The present study suggests that the HME and FMP co-exist, and, furthermore, jointly affect people's voting behavior. More specifically, based on a media content analysis and a long-term panel survey surrounding the 2014 election for the European Parliament in the Netherlands, we find that people selectively turn to like-minded friendly media (FMP), but perceive coverage about the EU (European Union) in these media as relatively unsupportive of their own position (HME). In this context, the FMP and HME appear to jointly influence voting behavior. People cast votes in line with the objectively partisan-friendly media tone of their self-selected media. However, to a certain extent they do so, because they seem motivated to counteract the seemingly unfair or insufficient coverage about the EU.